Adults with autism spectrum disorder as behavior technicians for young children with autism: Outcomes of a behavioral skills training program. Issue 2 (14th April 2015) - Lerman, Dorothea C.; Hawkins, Lynn; Hillman, Conrad; Shireman, Molly; Nissen, Melissa A.
<x xml:space="preserve">Abstract</x> Adults with autism spectrum disorder (ASD), who were interested in working as behavior technicians for young children with autism, participated in 2 experiments. Participants included 5 adults with Asperger syndrome or pervasive developmental disorder not otherwise specified, 19 to 23 years old, and 11 children with autism, 3 to 7 years old. In Experiment 1, training of the adults focused on the implementation of mand training via incidental teaching. Experiment 2 focused on teaching participants to use discrete‐trial training (DTT) with children who exhibited problem behavior. Both experiments showed that behavioral skills training was effective for teaching the adult participants the behavioral procedures needed to teach children with autism. In addition, the children acquired skills as a result of training. Results of Experiment 2 further demonstrated that the DTT skills generalized across untrained targets and children. Social validity ratings suggested that some participants' teaching was indistinguishable from that of individuals without ASD.